Can Households be Multilocal? Conceptual and Methodological Considerations based on a Namibian Case Study - Greiner, Clemens (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
This contribution deals with circular migration, remittances and rural-urban support networks in Namibia’s southern Kunene region and with the question of how to conceptualise the household as a unit of analysis in the context of these dynamics. Based on an outline of the methodology used to gather quantifiable data on rural-urban exchange and empirical data, it focuses on the domestic unit and analyses its role in the context of high mobility and rural-urban networks. It offers a critique of the ‘multilocal household’ approach and suggests the concept of translocal livelihoods as an alternative approach.